Morphology of Pyramidal Neurons in the Rat Prefrontal Cortex: Lateralized Dendritic Remodeling by Chronic Stress - Claudia Perez-Cruz; Jeanine I. H. Müller-Keuker; Urs Heilbronner; Eberhard Fuchs; Gabriele Flügge (Neural Plasticity)
The prefrontal cortex (PFC) plays an important role in the stress response. We filled pyramidal neurons in PFC layer III with neurobiotin and analyzed dendrites in rats submitted to chronic restraint stress and in controls. In the right prelimbic cortex (PL) of controls, apical and distal dendrites were longer than in the left PL. Stress reduced the total length of apical dendrites in right PL and abolished the hemispheric difference. In right infralimbic cortex (IL) of controls, proximal apical dendrites were longer than in left IL, and stress eliminated this hemispheric difference. No hemispheric difference was detected in anterior cingulate cortex (ACx) of controls, but stress reduced apical dendritic length in left ACx. These data demonstrate interhemispheric differences in the morphology of pyramidal neurons in PL and IL of control rats and selective effects of stress on the right hemisphere. In contrast, stress reduced dendritic length in the left ACx.